Private Self-Consciousness and Self-Monitoring on Instagram: The Mediating Effect of Internal Locus of Control and Self-Concept. Issue 3 (3rd April 2021) - Ahadzadeh, Ashraf Sadat; Ong, Fon Sim; Wu, Shin Ling; Deng, Ruolan
Abstract: Past studies examining the direct relationship between private self-consciousness and online self-presentation behavior have not met with much success. The aim of this study was to examine the direct relationship between private self-consciousness and self-monitoring as well as the indirect relationship between these two variables through the mediation of locus of control and self-concept among Instagram users. Besides investigating locus of control and self-concept independently, serial mediation of locus of control and self-concept in the relationship between private self-consciousness and self-monitoring was also examined. A sample of 309 university students was conveniently drawn from three private universities in Kuala Lumpur, Malaysia. Participants completed a survey that collected data on private self-consciousness, internal locus of control, self-concept, self-monitoring on Instagram and relevant demographic data. Results of this study showed that there is no direct relationship between private self-consciousness and self-monitoring on Instagram. Independently, locus of control was found to mediate the relationship between private self-consciousness and self-monitoring while self-concept did not. The serial-multiple mediation test supported the mediating role of locus of control and self-concept on this relationship. These indirect relationships contribute to our understanding of the underlying mechanism through which private self-consciousness influences self-monitoring on Instagram.